2021
DOI: 10.3390/sym13101918
|View full text |Cite
|
Sign up to set email alerts
|

Chance and Necessity in the Evolution of Matter to Life: A Comprehensive Hypothesis

Abstract: Specialists in several branches of life sciences are trying to solve, piece by piece, the immensely complex puzzle of the origin of life. Some parts of the puzzle seem to appear with a rather high degree of clarity, while others remain totally obscure. We cannot be sure that life emerged only on our Earth, but we believe that the presence of large amounts of water in its liquid state is absolutely essential for the emergence and evolution of living matter. We can also assume that the latter exploits everywhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…A critical analysis of the terrestrial and extraterrestrial theories on the chirality of life 1,[4][5][6][7][8][9] has shown that, in all cases, various assumptions do not provide a key link in solving the challenge of homochirality, i.e., how to achieve a total shift in the chiral balance to obtain enantiopure biopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…A critical analysis of the terrestrial and extraterrestrial theories on the chirality of life 1,[4][5][6][7][8][9] has shown that, in all cases, various assumptions do not provide a key link in solving the challenge of homochirality, i.e., how to achieve a total shift in the chiral balance to obtain enantiopure biopolymers.…”
Section: Introductionmentioning
confidence: 99%